Profile of potential donor and family refusal to donate organs (Research, Society and Development, 2020)
To identify the profile of the potential donor of an Intra-Hospital Committee for Donating Organs and Tissues for Transplants in the extreme south of the country and the reasons for family refusal to donate organs and tissues for transplants. Retrospective quantitative study of documentary character, with data collection through 91 brain death protocols, between the years 2012 and 2017. Data were analyzed using descriptive statistics. Regarding family consent, a total of 47 negative and 44 positive family members for organ donation can be verified, resulting in the most frequent justification for family refusal, the ignorance of the decision of the potential donor, followed by conviction potential donor prior to not being an organ donor, followed by the preservation of the body's integrity. When tracing the profile of the potential donor, a greater predominance of males was identified, with an average age of 43 years and the Hemorrhagic Stroke as the cause of higher frequency of brain death. The description of the profile of the potential donor and the main reasons for family refusal can contribute to the planning and development of interventions that encourage the donation of tissues and organs.